Festuca marginata subsp. andresmolinae, subsp. nov. para la Península Ibérica. - Fuente García, Vicenta de la; Ortúñez Rubio, Emma (Botanica Complutensis, 1993)
FUENTE GARCíA, V. OB LA, & ORTUÑEZ Runio, E. 1993. Festuca marginata subsp. andresmolinae, subsp. nov. para la Península Ibérica. Bat Complutensis [8: 105-112 En este trabajo se describe un nuevo taxon, F. marginata subsp. andresmo/inae, en la Península Ibérica. Dedicamos eí mismo al Dr. Andrés Molina.